USING LEGO SCRAMBLE GAME AS MEDIA TO TEACH SIMPLE PAST TENSE ON NARRATIVE TEXT TO THE EIGHT GRADERS (RETAIN, 2017)
USING LEGO SCRAMBLE GAME AS MEDIA TO TEACH SIMPLE PAST TENSE ON NARRATIVE TEXT TO THE EIGHT GRADERS Setyo Pambudi Luhung Engish Literature, Faculty of Language and Arts, The State University of Surabaya setyopluhung@yahoo.co.id Dr. Oikurema Purwati, Eng. Grad. Dip, M.Appl. English Literature, Faculty of Language and Arts, The State University of Surabaya Pungki_unesa@yahoo.co.id ABSTRAK Dewasa ini banyak pembelajar bahasa mendapat kesulitan dalam mengaplikasikan grammar yang benar didalam menulis dan berbicara. Masalah bisa terjadi dalam tahapan pertama pendidikan mereka. Akan menjadi masalah bila guru mereka dalam sekolah menengah pertama tidak bisa menemukn cara yang pas untuk mengajarkan dasar grammar. Seperti yang kita tahu grammar adalah struktur dalam sistem kebahasaan. Nyatanya, peneliti menemukan bahwa beberapa guru di sekolah menengah pertama tidak bisa menemukan cara yang tepat untuk mengajarkan grammar. Ini akan menjadi masalah yang besar bagi mereka, ketika siswa merasa bosan dan akan menjadi sangat sulit bagi guru untuk menyampaikan materi mereka. Berdasarkan kenyaaan itu, peneliti mencoba menggambarkan permainan acak kata menggunakan lego sebagai media dalam pengajaran simple past tense di dalam teks narrative untuk kelas delapan sekolah menengah pertama, peneliti juga akan menggambarka respon siswa terhadap penerapanya. Penelitian ini adalah descriptive qualitative menggunakan 3 instrumen observasi, ceklis dan interview. Dia menggunakan dua kali treatment oleh guru. Datana akan di analisis secara qualitative. Hasilnya menunjukan acak kata menggunakan lego bisa menjadi salah satu alternatif dalam pengajaran simple past tense. Teknik ini membuat murid menjadi lebih engerti dala simple past tense dan membuat murid percaya diri dalam pembuatan narrative mereka sendiri. Dengan game ini murid bisa termotivasi untuk melatih kemampuan mereka dalam grammar dan menulis. Ini bisa menjadi catatan bahwa acak kata menggunakan lego bisa menjadi media pembelajaran untuk kelas tujuh. Penelti menyarankan guru lain untuk bisa menggunakan teknik ini sebagai cara alternativ dalam pembelajaran grammar di kelas sekolah menengah pertama. ABSTRACT Nowadays there are many language learners get difficulties in applied appropriate grammar on productive skill, such as speaking and writing. The problem might be occurring on their first education. It would be matter when the teacher on Junior high school does not give their students the appropriate method to teach their basic grammar. As we know grammar is the structure and system of a language. In reality, the researcher found that some teacher in junior high school cannot find the appropriate way to teach grammar. It would be such a big problem for them, when the junior high school student gets bored it would be very hard for the teacher to deliver their material. Based on the reality, the researcher described Lego scramble game as the media to teach simple past tense in narrative text to the seven graders, the researcher also describes the students’ responses toward the technique. This research is descriptive qualitative employing three instruments in order to get the data. Those are observation, checklist and interview. The treatment was given twice by the teacher. The data were analysed qualitatively. The result showed that “Lego” scramble game can be an alternative way to teach simple past tense. This technique made the student more understand about simple past tense and confident to write it on their own narrative text in appropriate way. Through this game the student will be motivated to exercise their skill in grammar and their writing. It could be summary that Lego scramble game could be used in the teaching learning process to the seventh graders. The researcher suggested that other teacher could use this game as their alternative way to teach grammar in junior high school. Key Words: “Lego” scramble game, reading, simple past tense, narrative text, eidght graders.